Factors influencing the financing decision: Multinational Company (MNC) listed in Bursa Malaysia / Norhairiah Husain - Husain, Norhairiah (2007)
This study focuses on the factors that influencing the financing decision for Multinational Companies listed in Bursa Malaysia from the year 2001 to 2005. According to encyclopedia, business enterprise with manufacturing, sales, or service subsidiaries in one or more foreign countries, is known as a transnational or international corporation. Typically, a multinational corporation develops new products in its native country and manufactures them abroad, often in Third World nations, thus gaining trade advantages and economies of tabor and materials. The study is used 39 selected companies that comprises of Industrial Product sector listed in Main Board. The objective or purpose of this study is to determine factors that are influencing financing decision. The selected indicators to be independent variables in this research are growth of company, profitability, ownership, and size of company. Meanwhile, for the dependent variable is the financing decision represent by debt ratio of the company. These factors have been considered to be the indicators as according to the past researches done by other researchers. This research was using Multiple Regressions where this method is an estimation of the parameter of an equation with more than one independent variable. The purpose is to show the relationship between dependent variable (debt) and the independent variables, which are growth of company, profitability, ownership, and size of company. The test is success to reject null hypothesis.